Benefits and risks of low molecular weight heparin use on reproductive outcomes: A retrospective cohort study - Ming Chen; Yi-Ting Chen; Chun-Min Chen; Wan-Ju Wu; Wen-Hsiang Lin; Gwo-Chin Ma (Elsevier, 2022)
Objective: Low molecular weight heparin (LMWH) has been given to reproductive-age women with various indications. This study aims to assess the benefits and risks of such use. Materials and methods: We retrospectively reviewed data (n = 204) between Jan 2016 and May 2019. Logistic regression analysis was conducted to evaluate the correlation between indications and reproductive outcomes. Results: LMWH use had higher odds of live birth in women less than 30 years of age (OR: 4.98; 95% CI = 1.13-21.98; p = 0.034) and with protein S deficiency (OR: 3.90; 95% CI = 1.77-8.59; p = 0.001). For the subgroup of recurrent pregnant loss, LMWH use was only advantageous to women with protein S deficiency (OR: 2.45; 95%:1.01-5.97; p = 0.048). Risks such as preterm delivery, small-for-gestational-age, placental abruption, antepartum/postpartum hemorrhage were not significantly increased among subgroups. Women treated with LMWH and who had successful live births (n = 171) had a slightly increased risk of postpartum hemorrhage compared to controls (n = 8058) during this period in our institution (2.9% vs 1.2%, p < 0.001). Conclusion: LMWH administration produces a higher chance of live-birth to women younger than 30 years of age or with protein S deficiency. However, risk of postpartum hemorrhage is increased.